1993
DOI: 10.1084/jem.178.1.279
|View full text |Cite
|
Sign up to set email alerts
|

Freezing adhesion molecules in a state of high-avidity binding blocks eosinophil migration.

Abstract: SummaryLeukocyte extravasation is mediated by multiple interactions of adhesive surface structures with ligands on endothelial cells and matrix components. The functional role of 31 (CD29) integrins (or very late antigen [VLA] proteins) in eosinophil migration across polycarbonate filters was examined under several in vitro conditions. Eosinophil migration induced by the chemoattractant C5a or platelet-activating factor was fully inhibited by monoclonal antibody (mAb) 8A2, a recently characterized "activating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1

Year Published

1997
1997
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(73 citation statements)
references
References 35 publications
(35 reference statements)
3
69
1
Order By: Relevance
“…To investigate the changes in intracellular free Ca 2ϩ of adherent eosinophils upon IL-8 and eotaxin stimulation, cells were incubated with 8A2 and loaded on fibronectin-coated cover slips or nontreated cells were loaded on 7-h TNF-␣-stimulated HUVEC (see Materials and Methods (35)). After stimulation with 10 Ϫ8 M IL-8, a clear increase in [Ca 2ϩ ] i (Ͼ 200 nM) was observed in 42 Ϯ 7% and 30 Ϯ 7% of the cells adhering to fibronectin and activated HUVEC, respectively (Fig.…”
Section: Eosinophils Bound To Fibronectin and Endothelium Show Signifmentioning
confidence: 99%
“…To investigate the changes in intracellular free Ca 2ϩ of adherent eosinophils upon IL-8 and eotaxin stimulation, cells were incubated with 8A2 and loaded on fibronectin-coated cover slips or nontreated cells were loaded on 7-h TNF-␣-stimulated HUVEC (see Materials and Methods (35)). After stimulation with 10 Ϫ8 M IL-8, a clear increase in [Ca 2ϩ ] i (Ͼ 200 nM) was observed in 42 Ϯ 7% and 30 Ϯ 7% of the cells adhering to fibronectin and activated HUVEC, respectively (Fig.…”
Section: Eosinophils Bound To Fibronectin and Endothelium Show Signifmentioning
confidence: 99%
“…Inhibition of migratory behavior in vivo or of motility in vitro occurs on induction of a high-avidity integrin binding conformation [55,62]. For thymocytes, the in vivo regulatory events that control the transition from strong adhesion via ␣ 5 ␤ 1 , to weak adhesion via both ␣ 4 ␤ 1 and ␣ 5 ␤ 1 , and to motility via either ␣ 4 ␤ 1 or ␣ 5 ␤ 1 , are as yet unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Activating mAbs to integrins increases adhesion [47,55,56,61]. Inhibition of migratory behavior in vivo or of motility in vitro occurs on induction of a high-avidity integrin binding conformation [55,62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that resting eosinophils adhere to fibronectin in a VLA-4-dependent manner and exhibit prolonged survival via autocrine production of cytokines such as GM-CSF (Anwar et al 1994, Neeley et al 1994, Walsh et al 1995. Other studies, however, have found little or no adhesion without prior activation with platelet-activating factor, Mn ++ or a β1 integrin-activating antibody (Kuijpers et al 1993, Kita et al 1996. A possible explanation for these discrepancies may arise from the fact that eosinophils express the β2 integrin Mac-1, and engagement through this receptor to a different site on fibronectin, or to the blocking protein (typically albumin), may be occurring.…”
Section: Eosinophil-extracellular Matrix (Ecm) In-teractions Through mentioning
confidence: 99%